Kierkegaard and mood disorders - Benning, Tony (Journal of spirituality in mental health, 2024)
With his writings encompassing such issues as depression, despair, faith, and hope, the nineteenth century Danish philosopher and theologian Søren Kierkegaard is known for his percipient insights into the psychology of spirituality. Here, the author presents a case from his psychiatric practice as a basis for exploring how Kierkegaard’s ideas can be drawn upon when providing spiritually orientated psychotherapy to clients suffering from depression. Kierkegaard’s ideas can inform the work of clinicians who are providing care to individuals with mood disorders regardless of whether it is being provided in the name of spiritually orientated psychotherapy, existential therapy, or pastoral counseling.